Sobre o comportamento em erosão-cavitação da liga Co30cr19fe nas condições metalúrgicas fundida, solubilizada, encruada e nitretada em baixa temperatura - Romero, Manuelle Curbani (2018)
The cavitation erosion behaviour of Co30Cr19Fe alloy as cast, solution treated, cold worked and low temperature nitrided was evaluated by vibratory cavitation tests and by its wear mechanisms. Damage evolution under cavitation attack was observed by scanning eletronic microscopy (SEM) and optical microscopy. The Co30Cr19Fe alloy results were compared to those of the comparison materials, AISI304 and Stellite 6.As cast sample have a mixture of phases α-FCC e ε-HCP and, after the test, exhibited an increase of the HCP fraction, showing the formation of strain-induced martensite. Solution treatment, at 1200°C for 8 hours and quenchingin water,resulted in athermal martensite formation, as well as a primary recrystallization.Low temperature nitriding, 350°C and 400°C, was done in solution treated and recrystallized samples, resulting in S phase formation with different width and CrN nitrides precipitation.It can be seen from the curve of cumulative mass loss versus cavitation exposure time that all conditions have higher cavitation erosion (CE) resistance than AISI 304. And, only solution treated and nitrided at 350°Csampleshave lower resistance than Stellite 6. Cold-rolling process increased incubation time in 55% and lowered wear rates in 53%. Low temperature nitriding at 400°C was the most effectivetreatmentatincrease CE resistance. Solution treated sample nitrided at this temperature showed the higher resistance, increasing 267% the incubation time and reducing in 5 times the maximum wear rate. S phase formation was followed by an hardness increase, 908 0,01,inhibiting plastic deformation and increasing materials elastic recovery, delaying stages thatlead to material removal.Wear process for this material is controlled by plastic deformation. Extensive development of slip bands, plastic extrusion of those bandsand wear from these strained regions were verified in all samples. Secondarily, material removal takes place from grain boundaries and triangular arrays of martensite. Twin boundaries are preferably eroded and have a harmful effect.